Reflections on responsive public administration in Hong Kong the citizen's character, performance pledges and beyond. - Jack Man Keung Lo (1993)
"Administrative responsiveness and the quality of service delivery have increasingly become important issues in public sector management around the world. This article addresses these pledges by: (a) examining some of the core elements of the Citizen's Charter and its historical and theoretical antecedents; (b) exploring the salient issues and problems pertaining to the adoption and implementation of the pledges; and (c) assessing the significance of the pledges in the light of other public sector reform initiatives. The article also provides some pointers on the likely future direction of the public sector reform movement in Hong Kong"
Keywords: Public administration - Hong Kong